(untitled) (American Journal of Islam and Society, 2011)
In her book, Ingvild Flaskerud once and for all dispels the idea that Islam lacks and opposes all forms of visual art. Hers is a pioneering work, which guides her readers through Twelver Shi‘i visual culture in Iran. She frames her discussion by drawing on semiotic theory, particularly Charles Sanders Peirce and Roland Barthes, in order to show both the interpretive possibilities inherent in visual piety and the ways in which meaning is fixed. Flaskerud is uniquely positioned for writing about visual piety, as she has already produced an artistic visual film (“Standard Bearers of Hussein: Women Commemorating Karbala,” 2003) on Shi‘i women’s practices in Iran. Visualizing Belief and Piety in Iranian Shi‘ism is a Geertzian “thick description” (Geertz, The Interpretation of Cultures) composed of three parts, each of which is followed by black-and-white pictures analyzed in that part. The first two parts address two iconographic themes respectively. The third discusses the usage of pious art in votive practices and ritual spaces ...